Macromineral requirements of Holstein calves - Rodrigues, João Paulo Pacheco; Lima, Jéssika Carolina Moutinho; Castro, Marcelo Messias Duarte; Valadares Filho, Sebastião de Campos; Chizzotti, Mario Luiz; Campos, Mariana Magalhães; Machado, Fernanda Samarini; Marcondes, Marcos Inácio (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to quantify the net requirements for the maintenance (NRm) and growth (NRg), as well as the retention coefficient (RC) of calcium, phosphorus, sodium, potassium and magnesium, of Holstein calves. The NRm were 87.8, 20.8, 4.36, 2.21, and 1.01 mg kg-1 of empty body weight for Ca, P, Na, K, and Mg, respectively. The RC was 0.882, 0.473, 0.274, 0.088, and 0.052 for Ca, P, Na, K, and Mg respectively. The requirements of Ca and P of Holstein calves are higher than those estimated for adult animals.